Extrusion dies for plastics and rubber - Michaeli, Walter; Hopmann, Christian (Hanser Publishers, 2016)
Provides a comprehensive account of the full range of dies used for extrusion of plastics and elastomers. The distinctive features of the various types of dies are described in detail. Expert advice on the configuration of dies is given, and the possibilities of computer-aided design, as well as its limitations, are demonstrated.